Globalization, Democratization and Asian Leadership: Power Sharing, Foreign Policy and Society in the Philippines and Japan - Santamaria, Matthew (Kasarinlan: Philippine Journal of Third World Studies; Vol 25 No 1-2 (2010): Political Economy of Ideas, 2010)
Review of Pollard, Vincent Kelly. 2004. Globalization, Democratization and Asian Leadership: Power Sharing, Foreign Policy and Society in the Philippines and Japan. Hants, England: Ashgate Publishing Limited. 203 pp.